142k views
2 votes
-3 (4-2x) = 4 - 2x I can't seen to get this one

User Josh Slate
by
5.4k points

1 Answer

5 votes

Let's see what to do buddy...


- 3(4 - 2x) = 4 - 2x

Subtract the sides of the equation minus( 4 - 2x ) :


- 3(4 - 2x) - (4 - 2x) = 0

Factoring ( 4 - 2x ) :


(4 - 2x)( - 3 - 1) = 0


(4 - 2x)( - 4) = 0

Divided the sides of the equation by -4


4 - 2x = 0

Subtract the sides of the equation minus 4


- 2x = - 4

Negatives simplified.


2x = 4

Divided the sides of the equation by 2


x = (4)/(2) \\


x = 2

_________________________________

And we're done...

Thanks for watching buddy good luck.

♥️♥️♥️♥️♥️

User John Li
by
5.5k points